PENGARUH KOMUNIKASI YANG EFEKTIF DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT LANGKAT NUSANTARA KEPONG KANTOR KEBUN GOHOR LAMA - Azmi, Nurul; Syahrial, Hery (JKBM (JURNAL KONSEP BISNIS DAN MANAJEMEN), 2016)
This research aims to determine : 1)The effect of Effective Communication on Performance Employee in PT Langkat Nusantara Kepong Kantor Kebun Gohor Lama. 2) The effect of Motivation on Performance Employee in PT Langkat Nusantara Kepong Kantor Kebun Gohor Lama. 3) The effect of Effective Communication and Motivation on Performance Employee in PT Langkat Nusantara Kepong Kantor Kebun Gohor Lama. The Types of this research is associative research. Analysis technique of this research is multiple regression analysis. Population of this research are the 56 employees at PT Langkat Nusantara Kepong Kantor Kebun Gohor Lama. The technique of sampling used boring sampling. This research data sourced from primary data and process data collection using questionnaires. The result of this research are : As partially effective communication variable has positive effect and significant on performance employee variable, on the value of partial test is (3.807 > 1.674). Motivation variable has positive effect and not significant on performance employee variable, on the value of partial test is (1.082 < 1,674). And as simultantly effective communication and motivation have positive effect and significant on performance employee, on the value of simultantly test is (13.735 > 3.17).Keyword : Effective Communication, Work Motivation, Performance Employe.